Lessons Learned from the Medical Education during the Covid-19 Pandemic for Future Training of Indonesian Doctors - Maria Meiwati Widagdo (Faculty of Medicine Universitas Kristen Duta Wacana, 2022)
Lessons learned from the experiences gained from the pandemic can benefit future medical education. Blended learning to educate more students without sacrificing quality may be an effective alternative.